DIGITAL ENTREPRENEURSHIP IN THE ERA OF DIGITALIZATION: A LITERATURE REVIEW - Supit, Michella Christy Tania; Sumual, Shelty Deity Meity (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This research aims to examine the role of digitalization in driving the development of digital entrepreneurship amidst increasingly competitive global economic dynamics. Digitalization is seen as a strategic necessity for businesses to improve operational efficiency, expand market opportunities, and create added value through the use of technologies such as artificial intelligence, big data, and digital platforms. The method used in this research is a literature review, reviewing various scientific sources related to digitalization and digital entrepreneurship. The results of the study indicate that digitalization not only transforms traditional business models into more flexible and adaptive ones, but also enables the creation of new innovations, personalized services, and enhanced customer experiences. Furthermore, digitalization plays a crucial role in increasing business resilience, particularly in the face of crises such as the COVID-19 pandemic. Previous studies have revealed that the success of digital transformation is influenced by technological factors, socio-economic conditions, and institutional support, although challenges such as limited resources, technological readiness, and implementation complexity remain. The discussion also highlights the importance of digital ecosystems, technological infrastructure, and digital skills development as key factors in supporting the growth of digital entrepreneurship. Digital platforms and technological infrastructure provide opportunities for businesses to develop products, expand distribution, and improve business efficiency. In conclusion, digitalization is a key foundation for the development of modern entrepreneurship, encompassing various economic, social, and organizational aspects. Therefore, business actors are required to continuously adapt, improve digital competency, and optimally utilize technology to achieve business sustainability and competitiveness in the future.